Developing a Set of Learning Tools Based on Realistic Mathematics Education for Sequences and Series Assisted by MathCityMap in Islamic Boarding School - Hanifah Rizki Mubarokah; Didik Sugeng Pambudi; 3Nurcholif Diah Sri Lestari; Dian Kurniati; Abi Suwito (Riemann: Research of Mathematics and Mathematics Education, 2026)
Mathematics learning is essential for strengthening students’ logical reasoning and numeracy skills, particularly in abstract topics such as sequences and series; however, instructional practices in Islamic boarding schools often remain procedural and insufficiently contextualized, creating a gap between theoretical recommendations of meaningful learning and classroom reality. This study aims to develop and evaluate RME-based learning tools for sequences and series assisted by MathCityMap to determine their validity, practicality, and effectiveness in a pesantren context. The research employed a 4D development model consisting of Define, Design, Develop, and Disseminate stages. Implementation involving an experimental class and a control class, each comprising 34 students. Data were collected through expert validation sheets, observation instruments, questionnaires, interviews, and numeracy pretest-posttest assessments. The results show that all learning tools achieved valid criteria, with average expert scores above 3.75 on a four-point scale. Practicality was confirmed by 95% implementation fidelity, 84.9% active student participation, and highly positive teacher and student responses. Effectiveness testing revealed a moderate N-gain score of 0.65 in the experimental class compared to 0.54 in the control class, with an independent samples t-test indicating a significant difference (Sig. = 0.049 < 0.05). These findings demonstrate that integrating Realistic Mathematics Education with MathCityMap enhances conceptual understanding, engagement, and numeracy achievement in sequences and series learning within Islamic boarding schools.